Mercury's wings : exploring modes of communication in the ancient world - Naiden, F. S.; Naiden, F. S.; Talbert, Richard J. A.; Talbert, Richard J. A. (Oxford University Press, 2017)
'Mercury's Wings' is a volume of essays devoted to ancient communications. Comparable previous work has been mainly confined to articles on aspects of communication in the Roman empire. This set of 18 essays with an introduction by the co-editors marks a milestone, therefore, that demonstrates the importance and rich further potential of the topic